Patient characteristics and predictors of mortality associated with pericardial decompression syndrome: a comprehensive analysis of published cases. Issue 2 (1st April 2015) - Pradhan, Rajesh; Okabe, Toshimasa; Yoshida, Kazuki; Angouras, Dimitrios C; DeCaro, Matthew V; Marhefka, Gregary D
Abstract: Background: Pericardial decompression syndrome (PDS) is a rare and potentially fatal complication of pericardial drainage, either by needle pericardiocentesis or surgical pericardiostomy. It manifests with paradoxical hemodynamic deterioration and/or pulmonary edema, commonly associated with ventricular dysfunction. We sought to elucidate factors associated with mortality in PDS. Methods: MEDLINE was systematically searched for PDS case reports and case series published between 1983 and 2013. For this analysis, clinical variables, echocardiographic and hemodynamic variables, details of drainage procedure and clinical outcomes were collected for each case. Results: A total of 35 cases (12 male, 23 female) were identified. PDS developed after pericardiocentesis, pericardiostomy, or both, in 18, 16, and one patients, respectively. Cardiac tamponade was the indication in 33 cases (94%). The mean age was 47 ± 17 years. The mean amount of effusion drained was 888 mL. The minimum amount of effusion drained was 450 mL. The onset of PDS after the procedure varied widely, ranging from 'immediate' to 48 hours. Presentations included 10 (29%) with cardiogenic pulmonary edema without shock, 14 (40%) with left ventricular failure, three (9%) with right ventricular failure, seven (20%) with biventricular failure, and one (3%) with non-cardiogenic pulmonary edema. Ten patients (29%) died of PDS. Mortality was associated only with surgical drainage ( p <0.001). Severe LV dysfunction normalized in PDS survivors. Conclusions: PDS is a rare complication of pericardial drainage with a high mortality rate. Surgical pericardiostomy was associated with mortality in PDS.